Change in the prevalence of social isolation among the older population from 2010 to 2016: A repeated cross-sectional comparative study of Japan and England. (November 2020) - Tsuji, Taishi; Saito, Masashige; Ikeda, Takaaki; Aida, Jun; Cable, Noriko; Koyama, Shihoko; Noguchi, Taiji; Osaka, Ken; Kondo, Katsunori
Highlights: Social isolation among older populations is more severe in Japan than in England. The difference has further widened especially for women and younger older adults. Changes were primarily driven by weakened kinships in Japan. Social isolation has alleviated gradually in women 75 years and older in England. Abstract: Objective: To compare the change in the prevalence of social isolation from 2010 to 2016 between older populations in Japan, the most aging and socially isolated country, and England, a country known for advanced social isolation measures. Methods: Surveys from the Japan Gerontological Evaluation Study (JAGES) and the English Longitudinal Study of Aging (ELSA) included 70, 751 and 4134 participants, respectively, aged 65 years or older in 2010 and 94, 228 and 4295 participants in 2016. We assessed the social isolation of respondents on a scale from 0 to 5 points based on lack of social interactions with a spouse or partner, children, relatives, or friends and nonparticipation in any organization. Results: Results of two-way analysis of variance confirmed significant interactions (nation × period) in men and women aged 65–74 years and women aged 75 years or older. In JAGES, all had higher scores in 2016 compared to 2010 (1.64–1.76, 1.28–1.36, and 1.55–1.60 points, respectively). Furthermore, the proportions of those with lack of interaction with relatives increased (52.7%–58.9%, 31.5%–41.1%, and 25.2%39.2%, respectively). In ELSA, women aged 75 years or older demonstrated a significantly lower mean score in 2016 than in 2010 (1.40 vs. 1.21). No significant changes were observed in other groups. Conclusion: Social isolation among older adults is more severe in Japan than in England. The difference has widened, especially for women and younger older adults. This is attributed to the weakening relationships with relatives in Japan.